Clinical Impacts of ST- Segment Non-Resolution after Thrombolysis for Myocardial Infarction (University Heart Journal, 2019)
Streptokinase therapy for acute myocardial infarction reduces early mortality and improves outcomes. Failure of reperfusion after streptokinase therapy for acute myocardial infarction is common and indicates a poor prognosis. We investigated the clinical consequences of non-resolution of the ST segment after thrombolytic therapy for acute ST-elevation myocardial infarction, in 80 consecutive patients admitted to a coronary care unit. Failed thrombolysis was defined as